2021
DOI: 10.3389/fphys.2020.613398
|View full text |Cite
|
Sign up to set email alerts
|

Routine Chest X-Rays Are Inaccurate in Detecting Relevant Intrapulmonary Anomalies During Medical Assessments of Fitness to Dive

Abstract: Introduction: Intrapulmonary pathology, such as bullae or blebs, can cause pulmonary barotrauma when diving. Many diving courses require chest X-rays (CXR) or high-resolution computed tomography (HRCT) to exclude asymptomatic healthy individuals with these lesions. The ability of routine CXRs and HRCT to assess fitness to dive has never been evaluated.Methods: Military divers who underwent yearly medical assessments at the Royal Netherlands Navy Diving Medical Center, including CXR at initial assessment, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In particular since there has been continuous improvement in the quality and resolution of low-dose CT imaging over the last decades, and this trend is expected to persist in the upcoming years (Withers et al, 2021). As CT images become increasingly detailed, it is logical to anticipate the discovery of more findings of unknown clinical significance in (candidate) divers in the future, which, may lead to disqualifying even more divers, using current guidelines (Wingelaar et al, 2020;Bonnemaison et al, 2022). Visual presentation of location and number of bullae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular since there has been continuous improvement in the quality and resolution of low-dose CT imaging over the last decades, and this trend is expected to persist in the upcoming years (Withers et al, 2021). As CT images become increasingly detailed, it is logical to anticipate the discovery of more findings of unknown clinical significance in (candidate) divers in the future, which, may lead to disqualifying even more divers, using current guidelines (Wingelaar et al, 2020;Bonnemaison et al, 2022). Visual presentation of location and number of bullae.…”
Section: Discussionmentioning
confidence: 99%
“…In numerous standards, chest X-ray is still mentioned to exclude clinically relevant pulmonary pathology, but computed tomography (CT) for structural analysis of the pulmonary system has been shown a highly superior imaging technique ( Health and Safety Executive, 2023 ). However, higher-resolution CT scans in healthy individuals can uncover incidental findings of unknown clinical significance, raising concerns for its routine use in fitness to dive assessments in the general population ( Wingelaar et al, 2020 ; Bonnemaison et al, 2022 ). A forensic ( post mortem ) CT study in 130 adults without pulmonary injuries revealed that 33.8% of subjects had bullae/blebs ( de Bakker et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…A Dutch postmortem study of 130 adults aged 21-70 years and all causes of death found a 34% CT scans prevalence of emphysema blebs and bullae, increasing with age (de Bakker et al, 2020). A study conducted at the Royal Netherlands Navy Diving Medical Center compared the sensitivity of chest CT scan to chest radiography in asymptomatic male military subjects (Wingelaar et al, 2021). The characteristics of the study population were similar to those of our study, with subjects of mean age 36.4 years, compared with 25 years in our study.…”
Section: Prevalence Of Incident Emphysema Lesions In the General Popu...mentioning
confidence: 99%